Circulating GRP78 acts as a biomarker in the early diagnosis of lung cancer - Huang, Fang (Int J Clin Exp Pathol, 2018)
Glucose-regulated protein 78 (GRP78) is a major chaperone in endoplasmic reticulum (ER) and is increased in many types of malignant tumors. The role of GRP78 in early lung cancer diagnosis has not been clearly reported. The aim of this study is to detect the circulating level of GRP78 in the plasma of lung cancer patients and to evaluate the role of GRP78 in the early diagnosis of lung cancer. Plasma was collected from 251 lung cancer patients and 105 healthy controls, and the GRP78 expression in each sample was assayed using a commercially available ELISA kit. A receiver operating characteristic curve (ROC curve) was performed to analyze the role of GRP78 in lung cancer diagnosis. The combination of GRP78 and CEA, Cyfra21-1 was then analyzed using SPSS 17.0. The circulating level of GRP78 was increased dramatically in lung cancer patients (P < 0.0001) compared with the healthy controls. GRP78 provided a more sensitive and specific diagnosis than CEA in all lung cancer, ADC, and SCC patients, as well as in early (stage I) lung cancer patients. The results also indicated that a combination of GRP78, CEA and Cyfra21-1 could increase the accuracy of lung cancer diagnosis. GRP78 could be used as circulating biomarker in early lung cancer diagnosis.